2006
DOI: 10.1089/ten.2006.12.811
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Poly[Bis(Ethyl Alanato)Phosphazene] as a Scaffold for Bone Tissue Engineering

Abstract: Polyphosphazenes with amino acid ester as side groups are biocompatible polymers that could provide valid scaffolds for cell growth. In the present study we investigate the adhesion and growth of osteoblasts obtained from rat bone marrow on matrices composed of thin fibers of poly[bis(ethyl alanato)phosphazene] (PAlaP), poly(d,l-lactic acid) (PDLLA), or PAlaP/PDLLA blend. Our data show that scaffolds of PAlaP or PAlaP/PDLLA blend enhanced the cell adhesion and growth in comparison with that observed in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…This strong interaction would inhibit the adhered cell re-orientation, migration and the cellular phenotypic expression. 25 Work is under progress to further improve the osteogenicity of PNEPhA scaffolds suitable for bone tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…This strong interaction would inhibit the adhered cell re-orientation, migration and the cellular phenotypic expression. 25 Work is under progress to further improve the osteogenicity of PNEPhA scaffolds suitable for bone tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, we have already observed that electrospun scaffolds of PPhe-GlyP (presenting the same porosity and fiber diameter of the scaffold here used) were able to improve both adhesion and proliferation of neuromicrovascular endothelial cells (Carampin et al, 2007). Moreover, poly[bis(ethyl alanato)phosphazene] (PAlaP) enhanced osteoblast attachment and growth compared with that observed on tissue culture polystyrene plates (Conconi et al, 2006). Taken together, these findings indicate that the cellular response to materials may depend on cell type.…”
Section: In Vitro Studies Of Pphe-glyp Scaffolds Obtained By Electrosmentioning
confidence: 80%
“…A number of synthetic biodegradable polymers have been subjected to electrospinning for providing a 3D nanofibrous scaffolds for better cell growth and tissue formation. For the purpose of regenerative medicine, poly (α-hydroxy acids) [15], poly (propylene fumarate) [16], poly (orthoester) [17], polycarbonate [18], polyurethanes [19,20] poly-3-hydroxybutyrate [21], and polyphosphazenes [22] synthetic polymers were fabricated into nanofibrous scaffolds and characterized. Out of these synthetic biodegradable polymers, poly (α-hydroxy acids) including poly (lactic acid), poly (glycolic acid), and their copolymer poly(lactic acid-co-glycolic acid) have approved by FDA for certain regenerative medicine applications [23].…”
Section: Synthetic Polymers For Regenerative Medicinementioning
confidence: 99%